Antioxidant activity of an aqueous leaf extract from Uncaria tomentosa and its major alkaloids mitraphylline and isomitraphylline in Caenorhabditis elegans - Cestari de Azevedo, Bruna; Roxo, Mariana; Wink, Michael (Molecules, 2019)
Uncaria tomentosa (Rubiaceae) has a recognized therapeutic potential against various diseases associated with oxidative stress. The aim of this research was to evaluate the antioxidant potential of an aqueous leaf extract (ALE) from U. tomentosa, and its major alkaloids mitraphylline and isomitraphylline. The antioxidant activity of ALE was investigated in vitro using standard assays (DPPH, ABTS and  FRAP), while the in vivo activity and mode of action were studied using Caenorhabditis elegans as a model organism. The purified alkaloids did not exhibit antioxidant effects in vivo. ALE reduced the accumulation of reactive oxygen species (ROS) in wild-type worms, and was able to rescue the worms from a lethal dose of the pro-oxidant juglone. The ALE treatment led to a decreased expression of the oxidative stress response related genes sod-3, gst-4, and hsp-16.2. The treatment of mutant worms lacking the DAF-16 transcription factor with ALE resulted in a significant reduction of ROS levels. Contrarily, the extract had a pro-oxidant effect in the worms lacking the SKN-1 transcription factor. Our results suggest that the antioxidant activity of ALE in C. elegans is independent of its alkaloid content, and that SKN-1 is required for ALE-mediated stress resistance.
Gesehen am 31.10.2019